CASE REPORTClinical application of Nuss procedure for chest wall deformity in Poland syndrome - Koizumi, Tomoe; Mitsukawa, Nobuyuki; Saiga, Atsuomi; Satoh, Kaneshige (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
A 6-year-old girl with Poland syndrome was diagnosed with loss of hard and soft tissue on her affected chest. She required chest reconstruction to protect her thorax and improve her developmental delay. We applied a titanium device used for children with funnel chest to her, resulting in good shape. By using this device, we avoided sacrificing healthy rib and muscle; she could save the tissue for secondary surgery in puberty. The device made it possible to support the growth of her thoracic frame and has kept it in good shape. Also, 66 months after removing the device, her chest contour has been maintained. We evaluated the change of her chest frame by comparing the preoperative and postoperative CT index and found the result quite an improvement. We suggest that our technique would be easy, of low invasiveness, and safe for treatment of thoracic deformity in school age.